2015
DOI: 10.3402/qhw.v10.28157
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of changes in health complaints before, during, and after removal of dental amalgam

Abstract: In this article, we explore how patients with health complaints attributed to dental amalgam experienced and gave meaning to changes in health complaints before, during, and after removal of all amalgam fillings. We conducted semistructured qualitative interviews with 12 participants from the treatment group in a Norwegian amalgam removal trial. Interviews took place within a couple months of the final follow-up 5 years after amalgam removal. Using the NVivo9 software, we conducted an explorative and reflectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study from a referral institution found that patients reporting health deteriorations had altered mercury concentrations in erythrocytes and plasma, compared to patients who reported improvement of health status after amalgam removal [ 29 ]. Sjursen et al [ 30 ] concluded in a qualitative study that: “The dental amalgam was certainly important to get rid of, but it is uncertain how important the removal was for the experienced changes in health complaints”. Also Nerdrum et al [ 13 ], who reported improvement of health after amalgam removal, state that the amalgam might not have been the main cause of the patient’s subjective health complaints.…”
Section: Discussionmentioning
confidence: 99%
“…A study from a referral institution found that patients reporting health deteriorations had altered mercury concentrations in erythrocytes and plasma, compared to patients who reported improvement of health status after amalgam removal [ 29 ]. Sjursen et al [ 30 ] concluded in a qualitative study that: “The dental amalgam was certainly important to get rid of, but it is uncertain how important the removal was for the experienced changes in health complaints”. Also Nerdrum et al [ 13 ], who reported improvement of health after amalgam removal, state that the amalgam might not have been the main cause of the patient’s subjective health complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of illness, disease, and sickness, and what they represent, are not immutable, but they change over time (Johanisson, 1997). Sjursen et al (2015) suggested that the most important aspects of the amalgam controversy were found in the difference between the rational understanding of multifactorial explanations of health and the emotions around the questions about dental amalgam. This underscores the importance of health care professionals learning more about how patients think, act, and feel regarding illness attributed to dental restorations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a proportion of people experience health complaints, which they attribute to amalgam [2][3][4]. Moreover, for some of these patients the health complains persist even after removal of amalgam fillings.…”
Section: Introductionmentioning
confidence: 99%